Deconstructing Western Discourse: Sara Mills’ Analysis of Muslim Women in European News - Purwanto, Anim (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
The phenomenon under investigation is how European media frames Muslim women in its reporting, often trapped in stereotypes and misrepresentations. The aim of this study is to critically examine the representation of Muslim women in Europe in news texts. This study uses a critical discourse analysis method, adapting Sara Mills' deconstruction theory, which focuses on how the position of Muslim women actors is constructed through media representation. The data sources include news articles covering Muslim women in several European media outlets over the past five years. The data is analyzed by identifying discourse patterns that form the dominant representation of them and deconstructing these narratives to reveal how existing ideologies influence public understanding. The findings suggest that veiled Muslim women face systemic discrimination in the European labor market, particularly in countries like Germany and the Netherlands, which challenges the principle of religious neutrality and calls for urgent policy reform. At the intersection of gender and religion, they are especially vulnerable to structural inequalities, with dominant narratives often framing them as